Visual impairment is associated with depressive symptoms-results from the nationwide german DEGS1 dtudy - Schuster, Alexander K.; Tesarz, Jonas; Rezapour, Jasmin; Beutel, Manfred; Bertram, Bernd; Pfeiffer, Norbert (Frontiers in psychiatry, 2018)
Introduction: Visual impairment is associated with a variety of co-morbidities including physical and mental health in industrial countries. Our aim is to examine associations between self-reported impairment and depressive symptoms in the German population. Methods: The point prevalence of self-reported visual impairment in Germany was computed using data from the German Health Interview and Examination Survey for adults from 2008 to 2011 (N=7.783, 50.5% female, age range 18-79 years). Visual impairment was surveyed by two questions, one for seeing faces at a distance of 4 meters and one for reading newspapers. Depressive symptoms were evaluated with the PHQ-9 questionnaire and two-week prevalence was computed with weighted data. Depressive symptoms were defined by a value of ≥10. Logistic regression analysis was performed to analyze an association between self-reported visual impairment and depressive symptoms. Multivariable analysis including adjustment for age, gender, socio-economic status and chronic diseases were carried out with weighted data. Results: The two-week prevalence of depressive symptoms was 20.8% (95%-CI: 16.6 - 25.7%) for some difficulties in distance vision and 14.4% (95%-CI: 7.5 - 25.9%) for severe difficulties in distance vision, while 17.0% (95%-CI: 13.3 - 21.4%) resp. 16.7% (95%-CI: 10.7 - 25.1%) for near vision. Analysis revealed that depressive symptoms were associated with self-reported visual impairment for reading resp. with low visual impairment for distance vision. Multivariable regression analysis including potential confounders confirmed these findings. Conclusions: Depressive symptoms are a frequent finding in subjects with difficulties in distance and near vision with a prevalence of up to 24%. Depressive comorbidity should therefore be evaluated in subjects reporting visual impairment.
Gesehen am 28.08.2019